Investment and welfare implications of the ownership structure of overlapping networks - Brito, D.; Pereira, P. (Information Economics and Policy, 2008)
We analyze the impact of the ownership structure of cable television firms on the incentives to upgrade the cable networks to offer telecommunication services. First, we show that dual ownership of a local telephone network and a cable network, compared with separate ownership, may increase or decrease incentives to invest in upgrading the cable television network. Coordination economies benefit dual ownership, and business-stealing benefits separate ownership. Second, we perform a welfare analysis of the investment decision and third, a welfare analysis of the ownership structure.